Variasi bahasa pada mahasiswi rantau Asal Boyolali Jurusan Pendidikan Bahasa dan Sastra Indonesia Universitas Brawijaya - Ashidiqie, Tsamara Salwa (Aksara: Jurnal Bahasa dan Sastra, 2023)
Language variations can occur not only due to speakers of various languages, but also caused by diverse social interactions and covers a very wide environment. Universitas Brawijaya is one of the universities located in the city of Malang that has students with various cultural backgrounds. This study aims to examine what are the forms of language variations that occur in overseas students from Boyolali, Department of Indonesian Language and Literature Education, Universitas Brawijaya in the process of social interaction. The research method used in this research is descriptive qualitative with case study analysis on a sample. The sample in this study is Syaharani Savia who is an overseas student of Indonesian Language and Literature Education Universitas Brawijaya who comes from Boyolali. The results of this study are that there are several language variations that occur in the object of research, including Javanese dialect of Surakarta, Javanese dialect of Malang, English, slang, and Indonesian. The factor of the occurrence of language variations in the object of research is caused by the difference in the use of dialects in the Universitas Brawijaya environment with the environment of origin of the object of research and the situation of kinship between speakers.Keywords: sociolinguistics, language variation, nomadic students